THE USE OF EPA 5 MODEL IN EARLY READING LEARNING FIRST GRADE STUDENTS IN SDN 204 CIDADAP DISTRICTS CIDADAP BANDUNG CITY - Sri Kobilah; Lisna Lisna; Anugrah Ramadhan Firdaus (COLLASE (Creative of Learning Students Elementary Education), 2018)
This action research was motivated by the existence of problems in early reading learning in elementary schools. Early reading learning is not creative. Students are only instructed to memorize letters, words, and sentences in reading books, so that when students read simple sentences in writing, students are unable to read smoothly. The study was conducted in class I 204 Cidadap Elementary School with a total of 23 students. The research objectives were to: (1) describe the initial reading activities in class I by using the EPA 5 model for students in Class I of SD Negeri 204 Cidadap; (2) to find out the initial reading ability using the EPA 5 model for students of Class I of SD Negeri 204 Cidadap. This research was conducted with Classroom Action Research (PTK) method in three cycles. Data analysis was carried out in a qualitative way descriptively and quantitatively by searching for the average. Based on the research that has been done, the average value of students' initial reading activities in cycle I was 67.83, cycle II 72.17, and cycle III 76.52. Whereas reading ability in cycle I was 56.96, cycle II 69.13 and cycle III 80.00. It shows that the EPA 5 model can increase students' activities and abilities in learning to read early.